Diagnostic Accuracy of Endovaginal Scan in Detection of Retained Products of Conception after Incomplete Abortion - Kulsoom Iqbal, Sidra Manzoor, Rabia Waseem Butt, Manal Niazi, Ume Kulsoom, Umairah Kalim, Kulsoom Iqbal, Sidra Manzoor, Rabia Waseem Butt,Manal Niazi,Ume Kulsoom, Umairah Kalim (Journal of Rawalpindi Medical College, 2019)
Background : To determine diagnostic accuracy of Endo-vaginal Scan (EVS) in detection of retained products of conception (RPOC) in patients with incomplete abortion. Methods: In this prospective study 200 pregnant females, with gestational age <20 weeks and with persistent vaginal bleeding, diagnosed clinically with retained products of conception, were included. Endo-vaginal ultrasound scan pelvis was done in real time in axial and saggital planes. Imaging of the examination was directed towards evaluation of the uterus and any intrauterine contents. Endometrial thickness of >12mm on EVS was considered positive for diagnosis of RPOC which was later on confirmed with histopathology(HP) . Comparisons was then made between EVS and HP findings. Results: Mean age of selected patients was 30.8 years age ± 3.9 and mean gestational age 17.2 weeks ± 1.8 SD . Patients positive on EVS were 63.0% and patients positive on HP were 72.5%. Sensitivity, specificity, PPV, NPV and accuracy were found to be 71.7%, 60.0%, 82.5%, 44.6% and 68.5% respectively. Conclusion: Endovaginal ultrasonography allows detection of RPOC with reasonable accuracy.